Impact of Coronavirus disease-19 (COVID-19) lockdown on physical activity and energy expenditure among physiotherapy professionals and students using web-based open E-survey sent through WhatsApp, Facebook and Instagram messengers - Adarsh Kumar Srivastav, MPT; Neha Sharma, MPT; Asir John Samuel, MPT, PhD (Elsevier, 2021)
Background: Coronavirus disease - 19 (COVID-19) spread throughout the world and become pandemic. To stop and control the rapid infection of COVID-19 lockdown is the best option. Sudden lockdown implies change in entire lifestyle of the population. Social isolation affects individual's lives by greater reduction in their physical activity, which might increase the chance of infection by reducing immunity. To what extent, the physical activity is reduced during this lockdown period among physiotherapy professionals, and students who propagate physical activity is not known. Hence, we aimed to evaluate the impact of the COVID-19 lockdown on physical activity level and energy expenditure among physiotherapy professionals and students. Material and methods: One hundred and forty three volunteered physiotherapy professionals and students participated in web-based open E-survey. The survey was carried out by sending the Google Forms link for International Physical activity questionnaire-short form (IPAQ-SF) through social networking sites using Google Forms to gather the amount of PA before and during COVID-19 lockdown period and analysed using Wilcoxon signed rank test. Results: Among identified 261 potential survey participants, 143 responded, reaching a response rate of 54.8%. Total physical activity before and during COVID-19 lockdown period were 7809.7 (3849.7-11769.8) MET-min/week and 4135.7 (867.2-7404.1) MET-min/week; p < 0.0001. While energy expenditure before and during COVID-19 lockdown period were 8189.8 (4242.1-12137.6) kcal/wk and 4221.7 (1004.6-7438.8) kcal/wk; p < 0.0001. Conclusion: A significant reduction in self-report physical activity and energy expenditure levels were observed among physiotherapy professionals and students during the COVID-19 lockdown period.